Research on adherence of patients with type 2 diabetes mellitus and arterial hypertension to attainment of target levels of arterial pressure and the ways of patients’ adherence increase - I. N. Repinskaya; T. V. Ogir; E. M. Dolya; G. N. Koshukova; E. N. Primysheva; D. V. Shaduro; B. G. Cholah (Лечащий Врач, 2021)
The article reviews adherence to hypotensive therapy in patients with type 2 diabetes mellitus and arterial hypertension. In this research, the main non-compliance with hypotensive medications and their most common combinations are presented. Analysis of doctor’s recommendations for taking medications was made. We formulated recommendations for improving compliance in the DoctorPatient System.